2014
DOI: 10.1111/acem.12421
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Provider Preferences Related to Clinical Practice Guidelines for Tobacco Cessation: A Multicenter Survey

Abstract: Objectives To assess current emergency department (ED) provider practices and preferences for tobacco cessation interventions. The ED is an opportune place to initiate smoking cessation interventions. However, little is known about ED provider current practices and preferences for cessation counseling in the ED. Methods This was a survey of ED providers conducted in 2008–2009 (including physicians, nurse practitioners, physician assistants, and nurses), working at least half-time at ten U.S. academic EDs, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Also, the stress of completing acute care-related tasks during the visit due to time constraints was also identified. Lack of time and resources have been widely cited among ED/PED-based general preventive intervention research (e.g., vaccinations) [ 11 ] and tobacco control research [ 36 , 38 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the stress of completing acute care-related tasks during the visit due to time constraints was also identified. Lack of time and resources have been widely cited among ED/PED-based general preventive intervention research (e.g., vaccinations) [ 11 ] and tobacco control research [ 36 , 38 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, se encontró que el 98.38% considera que se debe realizar educación médica continua en tabaquismo, similar a los hallazgos en otras encuestas que evalúan la necesidad de capacitación por parte del personal de salud y que revelan que más del 90% están de acuerdo con la implementación de este tipo de temas académicos (17,22,35,36); sin embargo, en Kirguistan solo el 63% de los médicos piensa que se requiere más información (37); lo cual se encuentra sustentado en que el entrenamiento a los profesionales de la salud aumentaba la asesoría con la estrategia de las 5As, sobre todo en brindar ayuda, donde el 79.1% de los médicos familiares que tenía entrenamiento en tabaquismo realizaba asesoría a los padres de niños con enfermedades respiratorias y cerca 85% de los profesionales de la salud a nivel de urgencias ofrecían ayuda y asesoría (29,38), cifra que concuerda con el hallazgo de Kats et al, que solo el 5.7% de las enfermeras y el 5.1% realizaba esta intervención antes del entrenamiento, comparado con los datos posteriores donde el 22.5% de las enfermeras y el 18.4% de los médicos realizó la intervención (39).…”
Section: Discussionunclassified
“…[3][4][5][6][7][8] Prior research has found tobacco cessation management to be unappealing to some ED providers. 9 This may be attributed to the lack of familiarity by physicians with tobacco cessation strategies and the few studies in emergency medicine literature. Although tobacco cessation screening and interventions in the ED setting have been discussed, recommended, and reported, 10-22 none have measured the success of an "opt-out" approach to a prescriptive intervention.…”
Section: Importancementioning
confidence: 99%
“…The few studies that have reported rates of tobacco use in patients seeking care in the emergency department have shown great variability in prevalence (21%–41%) and report that rates are greater than that of the general population 3‐8 . Prior research has found tobacco cessation management to be unappealing to some ED providers 9 . This may be attributed to the lack of familiarity by physicians with tobacco cessation strategies and the few studies in emergency medicine literature.…”
Section: Introductionmentioning
confidence: 99%